Convergence and function between Baltasar Lobo and Claudio Rodríguez (happiness, impulse and flight) - Ramos de la Torre, Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This article looks to examine the closeness and convergence that exists between the sculptures of Baltasar Lobo and the poems of Claudio Rodríguez from a few essential concepts: love, morality, improvement, landscape, matter, impulse, maternity, home, friendship, happiness… Aspects that define the works and function of these two creators, among which the presence of light in the fields of Zamora and the first human landscape that they lived in will be some of the key components to define their point of view and artistic acceptance. From there, we shall try to clarify the main artistic preoccupations surrounding the worldview and the function in each of them, as well as the guidelines that define the rules that govern their respective works, be it from the point of view of art or from that of poetry. Lines of creative action and concepts that, in turn, can lead to the confirmation of a world of conceptual convergence and closeness, in emotion as well as in motivation and creation, between these two countrymen.
Keywords: Light; love; morality